The first way of war: American war making on the frontier, 1607-1814 - Grenier, John (Cambridge University, 2013)
Publisher description: This book explores the evolution of American war, showing how the first war waged against Indian noncombatant populations and their agricultural resources became the standard method of war employed by early Americans and which ultimately defined their military heritage. The bloodthirsty American conquest of Indian communities east of the Mississippi River helps demonstrate how early Americans embraced warfare shaped by extravagant violence and focused on conquest. Grenier provides a major revision in understanding the place of warfare directed on noncombatants in the American military tradition, and his conclusions are relevant to understand US 'special operations' in the War on Terror.